Mineral profiles of powdered milk, yoghurt, ice cream and raw milk - Kibria, Sumya; Masum, AKM; Islam, MA; Rashid, Md Harun ur (Asian Journal of Medical and Biological Research, 2017)
The present study was undertaken to update the dairy food composition database of Bangladesh by studying the minerals profile of important milk and milk products. Major minerals such as Sodium (Na), Potassium (K), Calcium (Ca), Magnesium (Mg) and Phosphorus (P) contents of powdered milk, yoghurt, ice cream and raw milk of cows were investigated in this study. The research was conducted at the postgraduate laboratory of Dept. of Agricultural Chemistry, Bangladesh Agricultural University, Mymensingh. Na and K content were found by flame spectrophotometry method, Ca and Mg by EDTA titrimetric method and P by UV-visible spectrophotometric determination. One Way ANOVA (with p values) was done by using statistical analytical software Stata 12. ANOVA was coupled with Tukeys test that gives mean separation in case of significant difference among the samples. Concerning mean values, powdered milk contained the highest Na (3138.19 ppm), K (9394.47 ppm), Ca (7615.2 ppm), Mg (891.18 ppm) and P (11332.36 ppm), whereas, the lowest Na (93.09 ppm), K (463.39 ppm) and Ca (1362.72 ppm) were found in raw milk and the lowest Mg (267.35 ppm) and P (1673.99) were found in ice cream. Elemental composition varied significantly from product to product (p<0.05). From this study it could be concluded that major minerals are found highest in powdered milk and lowest in raw milk, whereas, yoghurt and ice cream contained intermediate level of minerals. Asian J. Med. Biol. Res. June 2017, 3(2): 294-297